Subcutaneous treprostinil in congenital heart disease-related pulmonary arterial hypertension. Issue 14 (7th February 2018) - Skoro-Sajer, Nika; Gerges, Christian; Balint, Olga Hajnalka; Kohalmi, Dora; Kaldararova, Monika; Simkova, Iveta; Jakowitsch, Johannes; Gabriel, Harald; Baumgartner, Helmut; Gerges, Mario; Sadushi-Kolici, Roela; Celermajer, David S; et al.
Abstract : Objective: To assess the efficacy and safety of subcutaneous treprostinil in adult patients with congenital heart disease (CHD)-associated pulmonary arterial hypertension (PAH) after 12 months of treatment. Methods: Consecutive adult patients with CHD–PAH received subcutaneous treprostinil to maximum tolerated doses in an observational study. Results: Advanced CHD–PAH patients with WHO class III or IV disease (n=32, age 40±10 years, 20 females) received treprostinil for suboptimal response to bosentan (n=12), WHO functional class IV disease (FC, n=7) or prior to bosentan approval (n=13). In the multivariate mixed model, mean increase in 6 min walk distance (6-MWD) from baseline to 12 months was 114 m (76; 152) (P<0.001). WHO FC improved significantly (P=0.001) and B-type brain natriuretic peptide decreased from 1259 (375; 2368) pg/mL to 380 (144; 1468) pg/mL (P=0.02). In those 14 patients who had haemodynamic data before and after initiation of treprostinil, pulmonary vascular resistance decreased significantly (from 18.4±11.1 to 12.6±7.9 Wood units, P=0.003). The most common adverse events were infusion-site erythema and pain. One patient stopped treatment because of intolerable infusion-site pain after 8 months of treatment. No other major treatment-related complications were observed. Five patients died during early follow-up, having experienced a decrease in their 6-MWD prior. Conclusions: Subcutaneous treprostinil therapy is generally safe and effective for at least 12 months and may be used in CHD-related PAH class III and IV.